Disparity in maternal, newborn and child health services in high focus states in India: a district-level cross-sectional analysis - Awasthi, Ashish (BMJ Open, 2016)
OBJECTIVES: To examine the level and trend in the coverage gap of a set of interventions of maternal and child health services using a summary index and to assess the disparity in usage of maternal and child health services in the districts of high focus states of India. DESIGN: Data for the present study are taken from the Annual Health Survey (AHS), 2010–2013 and Census of India, 2011. SETTINGS: This study used secondary data from states having higher mortality and fertility rates, termed as high focus states in India. PARTICIPANTS: District-level information regarding children aged 12–23 months and ever married women aged 15–49 years has been extracted from the AHS (2010–2013), and household amenities, female literacy and main workforce information has been obtained from the Census of India 2011. MEASURES: 2 summary indexes were calculated first for maternal and child health services and another for socioeconomic and development status, using data from AHS and Census. Cronbach's α was used to assess the internal consistency of the items used in the index. RESULTS: The result shows that the coverage gap is highest in Uttar Pradesh (37%) and lowest in Madhya Pradesh (21%). Converge gap and socioeconomic development are negatively correlated (r=−0.49, p=0.01). The average coverage gap was highest in the lowest quintile of socioeconomic development. There was an absolute change of 1.5% per year in coverage gap during 2009–2013. In regression analysis, the coefficient of determination was 0.24, β=−30.05, p=0.01 for a negative relationship between socioeconomic development and coverage gap. CONCLUSIONS: There is a significant disparity in the usage of maternal and child healthcare services in the districts of India. Resource-rich people (urban residents and richest quintile) are way ahead of marginalised people (rural residents and poorest quintile) in the usage of healthcare services.